Moses Mendelssohn, Germany's First Migrant. (April 2017) - Peterson, Brent O.
Abstract : Germans have only recently accepted the fact that they belong to a nation of immigrants; officially, they still maintain the myth that migration to Germany began during the economic miracle of the 1950s. The claim that Moses Mendelssohn was Germany's first migrant is a deliberate intervention into the debate over the role of migrants in German culture. Mendelssohn's significance and the reason that he can function as Germany's first migrant, is that, as an early and eloquent writer on the idea of integration and belonging, he was able to write himself into the center of the discourse about what it meant to be German as that discussion was beginning. His case could leverage a new opening into still contentious and unresolved debates on issues as diverse as the history of migration, the role of religion in national cultures, the limits of tolerance vis‐à‐vis Others, and the demands that a majority culture can legitimately place on migrant minorities.